International Network of Antibiotic Allergy Nations (iNAAN): Protocol for a type 2 hybrid effectiveness-implementation multicentre prospective cohort and target trial emulation study evaluating penicillin allergy delabeling via direct oral challenge - Elise A. Mitri; Luke R. Fletcher; Camille Paynter; Sara Vogrin; Fiona James; Irvin Ng; Natasha E. Holmes; Courtney Ierano; Jason A. Roberts; Suran L. Fernando; Marlena Klaic; Jason A. Trubiano (PLoS ONE, 2025)
Background Penicillin allergies are reported in 1 in 10 hospitalised patients globally and are associated with inferior patient and health service outcomes. However, more than 95% of low-risk penicillin allergies can be removed by direct oral challenge (DOC). Objective The International Network of Antibiotic Allergy Nations (iNAAN) aims to evaluate the utility of an audit and feedback (A&F) and education implementation strategy to increase the adoption of penicillin DOC in patients with a low-risk penicillin allergy, while concurrently assessing the impact of penicillin DOC on antibiotic prescribing and health service outcomes. Methods This is an international, multicentre type 2 hybrid effectiveness-implementation trial evaluating the widespread safety, clinical effectiveness and implementation of penicillin allergy delabeling via DOC, following penicillin allergy assessment using a purpose-built digital penicillin allergy toolkit within a smartphone application. The implementation strategy encompasses evaluation of co-designed digitally delivered bimonthly A&F reports to health services and clinicians, beginning a minimum of three months post site-activation, and optional education sessions that are delivered by the study team. The primary effectiveness outcome is the proportion of patients with a low-risk penicillin allergy that are delabeled following DOC. The primary implementation outcome is clinician adoption of the digital penicillin allergy toolkit within 6-months of site activation. Participants include adult patients who report a penicillin allergy and have undertaken a formalised penicillin allergy assessment, with or without DOC, at a participating health service. A target trial emulation approach will be used to analyse secondary effectiveness outcomes, including the impact of penicillin DOC on international antibiotic prescribing, infection-related and health service outcomes. Discussion This study protocol presents a type 2 hybrid effectiveness-implementation trial design that will provide high level evidence to aid widespread implementation of penicillin DOC. Trial registration ACTRN12623000484640 (https://www.anzctr.org.au/) (https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=385815&isReview=true).